2015
DOI: 10.1186/s12888-015-0435-8
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation for treatment-resistant mood disorders: a long-term naturalistic study

Abstract: BackgroundLimited therapeutic options are available for patients with treatment-refractory major depression who do not respond to routinely available therapies. Vagus nerve stimulation showed adjunctive antidepressant effect in chronic treatment resistant depression, even though available studies rarely exceed 2-year follow up.We report a naturalistic 5-year follow up of five patients who received VNS implant for resistant depression (3 patients with major depressive disorder and 2 with bipolar disorder).Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…In a recent naturalistic follow-up study conducted by Albert and colleagues on a sample of both unipolar and bipolar patients, similar results were observed [10]. To our knowledge, no further studies have investigated VNS properties over a follow-up period of 5 years.…”
Section: Dear Editorsupporting
confidence: 83%
“…In a recent naturalistic follow-up study conducted by Albert and colleagues on a sample of both unipolar and bipolar patients, similar results were observed [10]. To our knowledge, no further studies have investigated VNS properties over a follow-up period of 5 years.…”
Section: Dear Editorsupporting
confidence: 83%
“…For the treatment of epilepsy, VNS has been shown to reduce both seizure frequency and severity . In patients with MDD symptom severity is reduced, , though long‐term follow‐up is still ongoing .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these results, some studies reported a reduction in function and amount of T cells during schizophrenia (Steiner et al, 2010;Craddock et al, 2007). Evidence for the role of a nervous component in neuropsychiatry was shown by the use of vagus nerve stimulation (VNS) for treatment-resistant mood disorders such as depression (Albert et al, 2015). VNS is an FDA approved treatment that improves depressive symptoms (Albert et al, 2015;Fang et al, 2015;Shiozawa et al, 2014).…”
Section: Different Pathways Involved In the Neuroinflammatory Pathogementioning
confidence: 94%
“…Evidence for the role of a nervous component in neuropsychiatry was shown by the use of vagus nerve stimulation (VNS) for treatment-resistant mood disorders such as depression (Albert et al, 2015). VNS is an FDA approved treatment that improves depressive symptoms (Albert et al, 2015;Fang et al, 2015;Shiozawa et al, 2014). Hypofunction of the parasympathetic vagus nerve was also shown to be involved in the pathophysiology of schizophrenia (Bar et al, 2008(Bar et al, , 2005(Bar et al, , 2012Malaspina et al, 1997;Boettger et al, 2006;Ostermann et al, 2013).…”
Section: Different Pathways Involved In the Neuroinflammatory Pathogementioning
confidence: 96%